(untitled) (Fiep Bulletin - online, 2015)
The carried through physical activities in the aquatic environment had been adhered by a good part of the world-wide population, perhaps for consequence of this fact, let us can evidence a good number of academies specialized in aquatic exercises, and still the presence of this modality composing the structure of activities of the majority of the academies. In the current times, the traditional chlorinated water swimming pool comes losing the space for a new method of water treatment, the ionization. As this method is very new, a few researches is observed on the behavior of our body when immersed in this way. Objective: In view of the presented facts previously, the aim of the present study was to compare the behavior of the physiological variable (Heart hate) during a water exercise classes, done in chlorinated and ionized water swimming pools. Methodology: The present study was comparative as Thomas and Nelson (2002), with exploratory characteristics. Carried out on seven women volunteers, apparently healthful, according to ACSM (2000), with the average of age of 21,71 years. The instrument using for gauging was a heart hate monitor (BLITZ®), model FOCUS. Results: The gotten data had received treatment statistical the end to compare the average values of the surveyed of heart hate, as much in rest how much in exercise, in the two types of swimming pool, using the test t of Student to compare the two different types of water. It was gotten then as final results, significant difference (sig.p 0,005) only for the average values of the heart hate in exercise. Conclusion: The result found take us to conclude, respecting the limitations of the study, that the half liquid when treated by the ionized method, provides to a bigger resistance to the movement, increasing then the intensity of the exercise, for the direct relation of the intensity and density of the water, corroborating with the AEA (2001).